The 1st International E-Conference on Antioxidants in Health and Disease 2020
DOI: 10.3390/cahd2020-08612
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of Phenolic Compounds from Cocoa Shell Subjected to In Vitro Digestion and Its Antioxidant Activity in Intestinal and Hepatic Cells

Abstract: The cocoa shell is a by-product generated by the cocoa processing industry that could be used as a nutraceutical owing to the significant amounts of bioactive compounds it contains. This work aimed to study the bioaccessibility of phenolic compounds present in the flour (CSF) and an aqueous extract (CSE) from cocoa shells through an in vitro simulated digestion and to assess their antioxidant capacity in vitro by using intestinal and hepatic cell culture models (IEC-6 and HepG2 cells). The bioaccessibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…We have previously demonstrated the presence of NADPH oxidase in the vascular wall of systemic arteries and pulmonary arteries and the elimination of NO by locally produced superoxide anion [ 32 , 33 ]. Based on the previously demonstrated antioxidant actions of CSE in cell cultures [ 34 ], we assessed the capacity of the extract to scavenge basal superoxide anion, using the fluorescent indicator DHE in intact arteries. Our results indicate the capacity of CSE to reduce superoxide anion levels.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated the presence of NADPH oxidase in the vascular wall of systemic arteries and pulmonary arteries and the elimination of NO by locally produced superoxide anion [ 32 , 33 ]. Based on the previously demonstrated antioxidant actions of CSE in cell cultures [ 34 ], we assessed the capacity of the extract to scavenge basal superoxide anion, using the fluorescent indicator DHE in intact arteries. Our results indicate the capacity of CSE to reduce superoxide anion levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, phytochemicals in the cocoa shell present the potential ability to stimulate antioxidant enzymes, such as SOD (10.2-43.6%) and CAT (13.1-52.3%). Recently, several studies have demonstrated the ability of cocoa shell extracts rich in phenolic compounds in the prevention of ROS production [9,10,18].…”
Section: Phenolic Compounds From the Cocoa Shell Exhibit Reactive Oxy...mentioning
confidence: 99%
“…(13.1-52.3%). Recently, several studies have demonstrated the ability of cocoa shell extracts rich in phenolic compounds in the prevention of ROS production [9,10,18].…”
Section: Phenolic Compounds From the Cocoa Shell Exhibit Reactive Oxy...mentioning
confidence: 99%
“…Entretanto, dentre os compostos fenólicos que Comportamento semelhante foi observado por Barak et al (2019), em um estudo de bioacessibilidade com extrato de cranberry europeia, em que houve uma diminuição de aproximadamente 64% no teor de compostos fenólicos totais entre o extrato bruto e a fase intestinal. Cañas et al (2020) constataram que o conteúdo de compostos fenólicos totais presentes na farinha e no extrato de casca de cacau também foram significantemente maiores (p<0,05) que nas respectivas frações digeridas. Seraglio et al(2017) trabalhando com três tipos de melato de bracatinga brasileira, e utilizando a mesma metodologia de digestão do presente estudo, também verificaram uma diminuição na quantidade de compostos fenólicos após a digestão das três amostras.…”
Section: 3 2 432 Teor De Fenólicos Totais Do Extrato De Própolis E Frações Digeridasunclassified